Positive electrode active material, method for producing same, battery cell, battery device, electric device

CN122267113APending Publication Date: 2026-06-23JIANGSU CONTEMPORARY AMPEREX TECH LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411896183.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-20
Publication Date
2026-06-23

AI Technical Summary

Technical Problem

In the existing technology, lithium phosphate cathode active materials have poor conductivity and ion diffusion performance, resulting in unsatisfactory cycle performance and rate performance of battery cells.

Method used

Transition metal carbides are used as coating materials to coat the surface of lithium phosphate-containing substrates, combined with carbon materials as the core, to form a stable and uniform coating layer, which improves conductivity and dispersibility and enhances the cycle performance of battery cells.

Benefits of technology

By improving the conductivity and structural stability of the positive electrode active material, the cycle performance and electrochemical performance of the battery cell are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122267113A_ABST
    Figure CN122267113A_ABST
Patent Text Reader

Abstract

The application discloses a positive electrode active material and a preparation method thereof, a battery monomer, a battery device and a power utilization device. The battery monomer comprises a positive electrode sheet, the positive electrode sheet comprises a positive electrode current collector and a positive electrode film layer located on at least one side surface of the positive electrode current collector, the positive electrode film layer comprises a positive electrode active material, the positive electrode active material comprises a core and a coating material, the core comprises a carbon material and a lithium-containing phosphate with a chemical formula of LiFe 1‑x‑ y Mn x M y PO4, wherein 0≤x≤1, 0≤y<1, 0≤1‑x‑y≤1, M is selected from one or more of group IIA elements, group IIIA elements, group IVA elements and transition metal elements; the coating material is coated on at least part of the surface of the core, and the coating material comprises a transition metal carbide. The battery monomer provided by the application has improved cycle performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of battery technology, specifically to a positive electrode active material and its preparation method, a battery cell, a battery device, and an electrical device. Background Technology

[0002] Batteries are widely used in electronic devices such as mobile phones, laptops, electric vehicles, electric cars, electric airplanes, electric ships, electric car toys, electric toy ships, electric toy airplanes, and power tools.

[0003] In the development of battery cells, improving the cycle performance of battery cells is one of the urgent problems to be solved. Summary of the Invention

[0004] To address the aforementioned technical problems, this application provides a positive electrode active material and its preparation method, a battery cell, a battery device, and an electrical device.

[0005] In a first aspect, embodiments of this application provide a battery cell. The battery cell includes a positive electrode sheet, which includes a positive current collector and a positive electrode film layer located on at least one side of the positive current collector. The positive electrode film layer includes a positive electrode active material, which includes a core and a coating material. The core includes a carbon material and a material with the chemical formula LiFe. 1-x- y Mn x M y The lithium phosphate of PO4, wherein 0≤x≤1, 0≤y<1, 0≤1-xy≤1, and M is selected from one or more elements of Group IIA, Group IIIA, Group IVA, and transition metals; a coating material is coated on at least a portion of the surface of the core, and the coating material includes transition metal carbides.

[0006] In this embodiment, transition metal carbides are used as coating materials for lithium phosphate-containing substrates. This improves the conductivity of lithium phosphate and thus enhances the electrochemical performance of the battery cell. Simultaneously, due to their excellent hydrophilicity, transition metal carbides disperse well in aqueous solutions, are less prone to aggregation, and their good flexibility allows for the formation of a stable and uniform coating layer on the lithium phosphate substrate surface, thereby improving the cycle performance of the battery cell. Furthermore, in this embodiment, introducing carbon materials into the core further enhances the conductivity of the positive electrode active material. Simultaneously, by placing the carbon material within the core of the positive electrode active material, the weak bonding between the carbon material and the lithium phosphate substrate is improved through transition metal carbide coating, thereby enhancing the cycle performance of the battery cell.

[0007] In some embodiments, the lithium phosphate comprises secondary particles formed by the stacking of primary particles, wherein the carbon material coats at least a portion of the surface of the primary particles.

[0008] In some embodiments, the volume distribution particle size Dv50 of the primary particles is 50nm-600nm.

[0009] In some embodiments, the carbon material forms a carbon coating layer on at least a portion of the surface of the primary particles, the thickness of the carbon coating layer being 1 nm to 20 nm.

[0010] In some embodiments, the Raman spectrum of the carbon coating layer has G peaks and D peaks, and I D / I G It is 0.6-0.9.

[0011] In some embodiments, the carbon material in the core has a mass content of 0.5%-1.5%.

[0012] In some embodiments, the coating material forms a coating layer on at least a portion of the surface of the core, the coating layer having a thickness of 1 nm to 20 nm.

[0013] In some embodiments, the mass content of the transition metal carbide is 0.1%-1% based on the total mass of the positive electrode active material.

[0014] In some embodiments, the transition metal carbide includes one or more of titanium carbide, niobium carbide, vanadium carbide, and molybdenum carbide.

[0015] In some embodiments, the specific surface area of ​​the positive electrode active material is 10 m². 2 / g-20m 2 / g.

[0016] In some embodiments, the compaction density of the positive electrode active material is 1.9 g / cm³. 3 -2.4g / cm 3 .

[0017] In some embodiments, the resistivity of the positive electrode active material powder is 15 Ω·cm-550 Ω·cm.

[0018] Secondly, embodiments of this application provide a battery device, including a single battery cell from the first aspect of this application.

[0019] Thirdly, embodiments of this application provide an electrical device, including a battery cell from the first aspect of this application or a battery device from the second aspect of this application.

[0020] Fourthly, embodiments of this application provide a positive electrode active material, including a core and a coating material, wherein the core includes a carbon material and a coating material with the chemical formula LiFe. 1-x-y Mn x M y The lithium phosphate of PO4, wherein 0≤x≤1, 0≤y<1, 0≤1-xy≤1, and M is selected from one or more elements of Group IIA, Group IIIA, Group IVA, and transition metals; a coating material is coated on at least a portion of the surface of the core, and the coating material includes transition metal carbides.

[0021] In some embodiments, the lithium phosphate comprises secondary particles formed by the stacking of primary particles, wherein the carbon material coats at least a portion of the surface of the primary particles.

[0022] In some embodiments, the transition metal carbide includes one or more of titanium carbide, niobium carbide, vanadium carbide, and molybdenum carbide.

[0023] In some embodiments, the specific surface area of ​​the positive electrode active material is 10 m². 2 / g-20m 2 / g.

[0024] In some embodiments, the compaction density of the positive electrode active material is 1.9 g / cm³. 3 -2.4g / cm 3 .

[0025] In some embodiments, the resistivity of the positive electrode active material powder is 15 Ω·cm-550 Ω·cm.

[0026] Fifthly, embodiments of this application provide a method for preparing a positive electrode active material, comprising the following steps:

[0027] Provide carbon sources, transition metal carbides, and materials based on the chemical formula LiFe. 1-x-y Mn x M y PO4 provides a lithium phosphate-containing raw material, wherein 0≤x≤1, 0≤y<1, 0≤1-xy≤1, and M is selected from one or more elements of Group IIA, Group IIIA, Group IVA, and transition metals; the lithium phosphate-containing raw material includes at least one of iron and manganese sources, a lithium source, and a phosphorus source.

[0028] The iron source and / or manganese source are mixed with the carbon source for a first sintering treatment to obtain a first sintered material;

[0029] The first sintering material, the lithium source, the phosphorus source, and the transition metal carbide are mixed and subjected to a second sintering process to obtain the positive electrode active material.

[0030] According to the embodiments of this application, the method of the fourth aspect of this application can be used to prepare the positive electrode active material of the third aspect of this application.

[0031] In some embodiments, the step of providing transition metal carbides includes:

[0032] Provides transition metal carbide precursors;

[0033] The transition metal carbide precursor was mixed with a lithium salt and reacted in an acidic solution. After drying, the transition metal carbide was obtained.

[0034] In some embodiments, the mass ratio of the transition metal carbide precursor to the lithium salt is 1:(0.2-1).

[0035] In some embodiments, the carbon source has a mass content of 0.5%-1.5% based on the total mass of the first sinter.

[0036] In some embodiments, the mass content of the transition metal carbide is 0.1%-1% based on the total mass of the positive electrode active material. Attached Figure Description

[0037] To more clearly illustrate the technical solutions of the embodiments of this application, the accompanying drawings used in the embodiments of this application will be briefly described below. Obviously, the drawings described below are only some embodiments of this application. For those skilled in the art, other drawings can be obtained based on the drawings without creative effort.

[0038] Figure 1 The diagram shows the structural features of a vehicle provided in some embodiments of this application.

[0039] Figure 2 This is an exploded schematic diagram of a battery provided for some embodiments of this application.

[0040] Figure 3 for Figure 2 The diagram shows an exploded view of the battery module.

[0041] The accompanying drawings are not necessarily drawn to scale.

[0042] The reference numerals in the attached drawings are explained as follows: 1. Vehicle; 2. Battery unit; 3. Controller; 4. Motor; 5. Housing; 5a. First housing section; 5b. Second housing section; 5c. Reception space; 6. Battery module; 7. Battery cell. Detailed Implementation

[0043] The following detailed description, with appropriate reference to the accompanying drawings, specifically discloses embodiments of the battery cell, battery device, and power-consuming device of this application. However, unnecessary detailed descriptions may be omitted. For example, detailed descriptions of well-known matters and repetitive descriptions of practically identical structures may be omitted. This is to avoid unnecessarily lengthy descriptions and to facilitate understanding by those skilled in the art. Furthermore, the accompanying drawings and the following description are provided for the purpose of enabling those skilled in the art to fully understand this application and are not intended to limit the subject matter of the claims.

[0044] The "range" disclosed in this application is defined by a lower limit and an upper limit. A given range is defined by selecting a lower limit and an upper limit, which define the boundaries of a particular range. Ranges defined in this way can include or exclude endpoints and can be arbitrarily combined; that is, any lower limit can be combined with any upper limit to form a range. For example, if ranges of 60-120 and 80-110 are listed for a specific parameter, it is expected that ranges of 60-110 and 80-120 are also included. Furthermore, if minimum range values ​​of 1 and 2 are listed, and if maximum range values ​​of 3, 4, and 5 are listed, then the following ranges are all expected: 1-3, 1-4, 1-5, 2-3, 2-4, and 2-5. In this application, unless otherwise stated, the numerical range "ab" represents a shortened representation of any combination of real numbers between a and b, where a and b are real numbers. For example, the numerical range "0-5" indicates that all real numbers between "0-5" have been listed in this article; "0-5" is simply a shortened representation of these numerical combinations. Furthermore, when a parameter is stated as an integer ≥2, it is equivalent to disclosing that the parameter is, for example, an integer such as 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.

[0045] Unless otherwise specified, all embodiments and optional embodiments of this application may be combined with each other to form new technical solutions, and such technical solutions should be considered to be included in the disclosure of this application.

[0046] Unless otherwise specified, all technical features and optional technical features of this application may be combined to form new technical solutions, and such technical solutions shall be deemed to be included in the disclosure of this application.

[0047] Unless otherwise specified, all steps in this application may be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), indicating that the method may include steps (a) and (b) performed sequentially, or it may include steps (b) and (a) performed sequentially. For example, the mention that the method may also include step (c) indicates that step (c) may be added to the method in any order. For example, the method may include steps (a), (b), and (c), or it may include steps (a), (c), and (b), or it may include steps (c), (a), and (b), etc.

[0048] Unless otherwise specified, in this application, the terms "first," "second," etc., are used to distinguish different objects, rather than to describe a specific order or primary / secondary relationship.

[0049] In this application, the terms "multiple" or "various" refer to two or more kinds.

[0050] In the description of the embodiments of this application, unless otherwise specified, "above" or "below" the second feature can mean that the first feature is in direct contact with the second feature, or that the first feature is in indirect contact with the second feature through an intermediate medium. Furthermore, "above," "over," and "on top" can mean that the first feature is directly above or diagonally above the second feature, or simply that the first feature is at a higher horizontal level than the second feature. "Below," "below," and "under" the second feature can mean that the first feature is directly below or diagonally below the second feature, or simply that the first feature is at a lower horizontal level than the second feature.

[0051] Unless otherwise stated, the terms used in this application have the common meanings as commonly understood by those skilled in the art.

[0052] Unless otherwise stated, the values ​​of the parameters mentioned in this application can be determined using various testing methods commonly used in the art, for example, according to the testing methods given in the embodiments of this application. Unless otherwise stated, the test temperature for each parameter is 25°C.

[0053] The battery device mentioned in the embodiments of this application can be a single physical module comprising one or more battery cells to provide higher voltage and capacity. For example, the battery mentioned in this application can include battery cells, battery modules, or battery packs.

[0054] A single battery cell is the smallest unit that makes up a battery, and it can independently perform the functions of charging and discharging. When there are multiple battery cells, they are connected in series, parallel, or mixed connections through a busbar.

[0055] In some embodiments, the battery device may be a battery module; when there are multiple battery cells, the multiple battery cells are arranged and fixed to form a battery module.

[0056] In some embodiments, the battery device may be a battery pack, which includes a housing and individual battery cells, with the individual battery cells or battery modules housed within the housing.

[0057] In some embodiments, the housing may be part of the vehicle's chassis structure. For example, a portion of the housing may be at least a part of the vehicle's floor, or a portion of the housing may be at least a part of the vehicle's crossbeams and longitudinal beams.

[0058] In some embodiments, the battery device may be an energy storage device. Energy storage devices include energy storage containers, energy storage cabinets, etc.

[0059] The technical solutions described in the embodiments of this application are applicable to battery devices and electrical devices that use battery devices.

[0060] Battery devices can be used as the power source for electrical devices or as energy storage units for electrical devices. Electrical devices can be, but are not limited to, mobile devices (such as mobile phones, tablets, laptops, etc.), vehicles (such as pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems, etc.

[0061] Electrical devices can choose the type of battery device according to their usage needs, such as individual battery cells, battery modules, or battery packs.

[0062] For ease of explanation, the following embodiments will use a vehicle as an example of an electrical device.

[0063] Figure 1 The diagram shows the structural features of a vehicle provided in some embodiments of this application.

[0064] like Figure 1 As shown, a battery device 2 is installed inside the vehicle 1. The battery device 2 can be located at the bottom, front, or rear of the vehicle 1. The battery device 2 can be used to power the vehicle 1; for example, the battery device 2 can serve as the operating power source for the vehicle 1.

[0065] The vehicle 1 may also include a controller 3 and a motor 4. The controller 3 is used to control the battery device 2 to supply power to the motor 4, for example, for the power needs of the vehicle 1 during starting, navigation and driving.

[0066] In some embodiments, the battery device 2 can not only serve as the operating power source for the vehicle 1, but also as the driving power source for the vehicle 1, replacing or partially replacing fuel or natural gas to provide driving power for the vehicle 1.

[0067] Figure 2 This is a schematic diagram of a battery explosion provided for some embodiments of this application. For example... Figure 2 As shown, the battery device 2 includes a housing 5 and battery cells (not shown), with the battery cells housed within the housing 5.

[0068] The housing 5 is used to house individual battery cells, and the housing 5 can have various structures. In some embodiments, the housing 5 may include a first housing portion 5a and a second housing portion 5b, which overlap each other, and together define a housing space 5c for housing the individual battery cells. The second housing portion 5b may be a hollow structure with one end open, and the first housing portion 5a may be a plate-like structure, with the first housing portion 5a covering the open side of the second housing portion 5b to form a housing 5 with the housing space 5c; alternatively, both the first housing portion 5a and the second housing portion 5b may be hollow structures with one side open, with the open side of the first housing portion 5a covering the open side of the second housing portion 5b to form a housing 5 with the housing space 5c. Of course, the first housing portion 5a and the second housing portion 5b can have various shapes, such as cylinders, cuboids, etc.

[0069] To improve the sealing performance after the first housing part 5a and the second housing part 5b are connected, a sealing element, such as sealant or sealing ring, can also be provided between the first housing part 5a and the second housing part 5b.

[0070] Assuming that the first box section 5a covers the top of the second box section 5b, the first box section 5a can also be called the upper box cover, and the second box section 5b can also be called the lower box.

[0071] In battery device 2, there can be one or more battery cells. If there are multiple battery cells, they can be connected in series, in parallel, or in a mixed configuration. A mixed configuration means that multiple battery cells are connected in both series and parallel configurations. Multiple battery cells can be directly connected in series, in parallel, or in a mixed configuration, and then the whole assembly of multiple battery cells is housed in housing 5. Alternatively, multiple battery cells can first be connected in series, in parallel, or in a mixed configuration to form battery module 6, and then multiple battery modules 6 can be connected in series, in parallel, or in a mixed configuration to form a whole assembly, which is then housed in housing 5.

[0072] Figure 3 for Figure 2 The diagram shows an exploded view of the battery module.

[0073] like Figure 3 As shown, in some embodiments, there are multiple battery cells 7, which are first connected in series, parallel, or mixed to form a battery module 6. The multiple battery modules 6 are then connected in series, parallel, or mixed to form a whole and housed in a casing.

[0074] Multiple battery cells 7 in battery module 6 can be electrically connected through a busbar component to achieve parallel, series, or mixed connection of multiple battery cells 7 in battery module 6.

[0075] The battery cells mentioned in the embodiments of this application may include lithium-ion battery cells or sodium-ion battery cells.

[0076] The battery cell includes an electrode assembly. The electrode assembly can be a wound structure or a stacked structure, and the embodiments of this application are not limited to this.

[0077] Electrode assemblies generally include a positive electrode, a negative electrode, and a separator.

[0078] [Positive electrode plate]

[0079] In some embodiments, the positive electrode may include a positive current collector and a positive electrode film layer located on at least one side of the positive current collector, the positive electrode film layer including a positive active material.

[0080] As an example, the positive current collector has two surfaces opposite each other in its own thickness direction, and the positive electrode film layer is disposed on either or both of the two opposite surfaces of the positive current collector.

[0081] In some embodiments, the positive electrode active material may include one or more of lithium phosphate, layered lithium transition metal oxide, Prussian blue compounds, polyanionic compounds, and sodium transition metal oxide.

[0082] If the positive electrode active material is one or more of lithium phosphate and layered lithium transition metal oxide, then the positive electrode active material can be used in lithium-ion battery cells; if the positive electrode active material is one or more of Prussian blue compounds, polyanionic compounds, and sodium transition metal oxide, then the positive electrode material can be used in sodium-ion battery cells.

[0083] Lithium-phosphate cathode active materials possess a one-dimensional olivine structure with ion channels. Compared to other types of cathode active materials, they exhibit poor conductivity and a low lithium-ion diffusion coefficient, resulting in unsatisfactory cycle performance and rate capability of individual battery cells. Current methods to improve the conductivity and ion diffusion performance of lithium-phosphate cathodes primarily involve nano-sizing, surface coating, and ion doping. Surface coating involves coating the surface of a lithium-phosphate matrix with highly conductive materials to construct a conductive network, thereby enhancing the material's conductivity. The key to surface coating lies in the selection of the coating material. Currently, commonly used coating materials are primarily highly conductive carbon materials, such as graphene, carbon nanotubes, and carbon nanospheres. These carbon materials, after sintering, can coat the surface of phosphate active materials to form a conductive coating structure, thus improving the material's conductivity. However, these carbon materials also have certain shortcomings, especially their tendency to agglomerate in water-soluble solvents, resulting in poor dispersibility and difficulty in processing. Although dispersibility can be improved by adding dispersants, the slurry with added dispersants has weaker bonding force with the matrix material during the coating process, and the structure of the resulting coating layer is not very stable, making it difficult to effectively utilize the high conductivity of carbon materials.

[0084] In view of the above-mentioned technical problems, this application provides a positive electrode active material. By adjusting the coating structure of the lithium phosphate material, it can have a stable coating structure and good electrical conductivity, thereby improving the cycle performance of the battery cell.

[0085] In some embodiments, the positive electrode active material includes a core and a coating material, wherein the core includes a carbon material and a coating material having the chemical formula LiFe. 1-x-y Mn x M y The lithium phosphate of PO4, wherein 0≤x≤1, 0≤y<1, 0≤1-xy≤1, and M is selected from one or more elements of Group IIA, Group IIIA, Group IVA, and transition metals; a coating material is coated on at least part of the surface of the core, and the coating material may include transition metal carbides.

[0086] Transition metal carbides are binary compounds formed by transition metal elements and carbon. Their structural characteristic is that carbon atoms fill the tetrahedral cavities of a close-packed metal lattice, exhibiting good hydrophilicity, conductivity, and flexibility. In this embodiment, transition metal carbides are used as coating materials for lithium phosphate-containing substrates, which can improve the conductivity of lithium phosphate and enhance the electrochemical performance of the battery cell. Simultaneously, due to their good hydrophilicity, transition metal carbides can disperse well in aqueous solvents and are not prone to agglomeration. Furthermore, their good flexibility allows for the formation of a stable and uniform coating layer on the surface of the lithium phosphate substrate, thereby improving the cycle performance of the battery cell. Further, in this embodiment, introducing carbon material into the core can further enhance the conductivity of the positive electrode active material. Simultaneously, by placing the carbon material within the core of the positive electrode active material, the weak bonding between the carbon material and the lithium phosphate substrate can be improved through transition metal carbide coating, thereby enhancing the cycle performance of the battery cell.

[0087] In some embodiments, lithium-containing phosphates may include one or more of lithium iron phosphate, lithium manganese phosphate, lithium manganese iron phosphate, and their respective modified compounds.

[0088] In some embodiments, lithium phosphate may include secondary particles formed by the stacking of primary particles, and carbon material may coat at least a portion of the surface of the primary particles.

[0089] In this application, primary particles and secondary particles have meanings known in the art. Primary particles refer to particles that have not formed aggregates, while secondary particles refer to aggregated particles formed by the aggregation of two or more primary particles. Primary particles and secondary particles can be distinguished by taking SEM images using a scanning electron microscope (SEM).

[0090] After preparing the lithium phosphate-containing cathode active material, the particles are typically subjected to air jet milling to reduce their particle size. This increases the compaction density of the cathode active material, thereby improving energy density and coating quality to meet the performance requirements of the battery cell. During air jet milling, the accumulated primary particles are partially or completely separated, and the particle size of the secondary particles decreases. This results in new exposed surfaces on the cathode active material, increasing the contact area between the particles and the electrolyte. Because lithium phosphate has high reactivity with the electrolyte, it can lead to increased side reactions during charge-discharge cycles, affecting the cycle performance of the battery cell. In this embodiment, by coating the surface of the primary particles with carbon material, the damage to the coating layer on the surface of the lithium phosphate particles can be reduced during secondary particle milling. This allows the lithium phosphate-containing cathode active material to have higher structural stability, reduces side reactions between the cathode active material and the electrolyte after air jet milling, and improves the cycle stability of the battery cell.

[0091] In some embodiments, the volumetric particle size distribution (Dv50) of the primary particles can be 50 nm to 600 nm. For example, the volumetric particle size distribution (Dv50) of the primary particles can be 50 nm, 60 nm, 70 nm, 80 nm, 90 nm, 100 nm, 120 nm, 140 nm, 150 nm, 160 nm, 180 nm, 200 nm, 220 nm, 240 nm, 260 nm, 280 nm, 300 nm, 350 nm, 280 nm, 400 nm, 450 nm, 500 nm, 550 nm, 600 nm, or any range of the above values.

[0092] In some embodiments, a carbon coating layer is formed on at least a portion of the surface of the primary particles, and the thickness of the carbon coating layer can be 1 nm to 20 nm. Exemplarily, the thickness of the carbon coating layer can be 1 nm, 2 nm, 3 nm, 4 nm, 5 nm, 6 nm, 7 nm, 8 nm, 9 nm, 10 nm, 11 nm, 12 nm, 13 nm, 14 nm, 15 nm, 16 nm, 17 nm, 18 nm, 19 nm, 20 nm, or any range of the above values. Optionally, the thickness of the carbon coating layer can be 3 nm to 15 nm.

[0093] In this application, the thickness of the carbon coating layer can be measured using methods and equipment known in the art. For example, it can be measured using a transmission electron microscope (TEM). As an example, a primary particle coated with carbon material can be placed under a transmission electron microscope, and the thickness of the carbon coating layer on the surface of the primary particle can be measured. The thickness at different locations (e.g., 5 locations) can be measured, and the average value can be taken as the thickness of the carbon coating layer.

[0094] Limiting the thickness of the carbon coating layer on the surface of the primary particles to the above range is beneficial for the carbon material to form a stable coating layer structure on the surface of the primary particles, improving the bonding force and coating stability of the carbon material on the surface of the primary particles, and giving the positive electrode active material better cycle stability, thereby improving the cycle performance of the battery cell.

[0095] In some embodiments, the Raman spectrum of the carbon coating layer has D peaks and G peaks, and I D / I G It is 0.6-0.9.

[0096] In this application, I D The D peak (SP) in the Raman spectrum 3 Peak intensity of hybrid carbon atoms, I G The G peak (SP) in the Raman spectrum 2 Peak intensity of hybrid carbon atoms, I D and I GIt can be measured using instruments and methods not disclosed in this art. For example, it can be determined by Raman spectroscopy, measuring the Raman spectrum of the positive electrode active material powder, and then obtaining the Ic of the carbon coating layer by peak separation of the Raman spectrum. D and I G value. I D / I G The ratio of the D peak intensity to the G peak intensity represents the SP content in the carbon coating layer. 3 Hybridized carbon and SP 2 The ratio of hybrid carbon content reflects the degree of graphitization of the carbon coating. Specifically, I D / I G The smaller the ratio, the more SP in the carbon coating layer 3 The lower the hybrid carbon content, the better the SP 2 The higher the hybrid carbon content, that is, the higher the graphitization degree of the carbon coating layer, the higher the conductivity of the carbon coating layer.

[0097] By limiting the carbon coating layer I D / I G When the ratio is within the above range, the carbon coating layer can provide high conductivity, while maintaining a high ion pathway, improving ion transport performance, and thus improving the cycle performance of the battery cell.

[0098] In some embodiments, the mass content of carbon material in the core can be 0.5%-1.5%. Exemplarily, the mass content of carbon material in the core can be 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1.0%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, or any range of the above values. Optionally, the mass content of carbon material in the core can be 0.7%-1.3%.

[0099] Limiting the carbon content in the core within the aforementioned range allows the positive electrode active material to possess high conductivity while maintaining a high capacity. When the carbon content is low, the improvement in conductivity of the positive electrode active material is limited, resulting in weak conductivity. Conversely, when the carbon content is high, the proportion of active material decreases, which is detrimental to increasing the capacity of the battery cell.

[0100] In some embodiments, the coating material forms a coating layer on at least a portion of the surface of the core, and the thickness of the coating layer can be 1 nm to 20 nm. Exemplarily, the thickness of the coating layer can be 1 nm, 2 nm, 3 nm, 4 nm, 5 nm, 6 nm, 7 nm, 8 nm, 9 nm, 10 nm, 11 nm, 12 nm, 13 nm, 14 nm, 15 nm, 16 nm, 17 nm, 18 nm, 19 nm, 20 nm, or any range of the above values. Optionally, the thickness of the coating layer can be 3 nm to 15 nm.

[0101] Transition metal carbides are used as coating materials to form a coating layer on at least part of the surface of the core. By limiting the thickness of the coating layer within the above range, the positive electrode active material can have higher electrical conductivity and structural stability, which is beneficial to further improve the cycle stability of the positive electrode active material and thus improve the cycle performance of the battery cell.

[0102] In this application, the thickness of the coating layer can be measured using methods and equipment known in the art. For example, it can be measured using a transmission electron microscope (TEM). As an example, secondary particles coated with transition metal carbides can be placed under a transmission electron microscope to measure the thickness of the coating layer on the surface of the secondary particles. The thickness at different locations (e.g., 5 locations) can be measured, and the average value can be taken as the thickness of the coating layer.

[0103] In some embodiments, the mass content of transition metal carbides can be 0.1%-1% based on the total mass of the positive electrode active material. Exemplarily, the mass content of transition metal carbides can be 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1.0%, or any range of the above values, based on the total mass of the positive electrode active material. Optionally, the mass content of transition metal carbides can be 0.3%-0.8% based on the total mass of the positive electrode active material.

[0104] Limiting the mass content of transition metal carbides in the positive electrode active material to within the aforementioned range is beneficial for improving the conductivity of the positive electrode active material while simultaneously achieving a higher specific capacity. When the transition metal carbide content is high, the proportion of active material decreases, resulting in a lower specific capacity of the positive electrode active material, which is detrimental to the capacity utilization of the battery cell. Conversely, when the transition metal carbide content is low, the stability of the resulting coating layer is poor, and its effect on improving the conductivity of the positive electrode active material is limited, leading to lower conductivity and poorer cycle performance of the battery cell.

[0105] In some embodiments, the transition metal carbide may include one or more of titanium carbide (Ti3C2), niobium carbide (NbC), vanadium carbide (VC), and molybdenum carbide (MoC).

[0106] In some embodiments, the specific surface area of ​​the positive electrode active material can be 10 m². 2 / g-20m 2 / g. For example, the specific surface area of ​​the positive electrode active material can be 10m². 2 / g、11m 2 / g、12m 2 / g、13m 2 / g、14m 2 / g, 15m2 / g, 16m 2 / g、17m 2 / g、18m 2 / g、19m 2 / g、20m 2 / g, or any range of the above values. Optionally, the specific surface area of ​​the positive electrode active material can be 12.5m². 2 / g-18m 2 / g.

[0107] In some embodiments, the compaction density of the positive electrode active material can be 1.9 g / cm³. 3 -2.4g / cm 3 For example, the compaction density of the positive electrode active material can be 1.9 g / cm³. 3 2.0g / cm 3 2.1g / cm 3 2.2g / cm 3 2.3g / cm 3 2.4g / cm 3 , or a range consisting of any of the above values.

[0108] In some embodiments, the resistivity of the positive electrode active material powder is 15 Ω·cm to 550 Ω·cm. Optionally, the resistivity of the positive electrode active material powder is 20 Ω·cm to 200 Ω·cm.

[0109] In this application, compaction density, volumetric particle size Dv50, and powder resistivity are all terms known in the art and can be measured using methods and instruments known in the art.

[0110] For example, compaction density can be determined using an electronic pressure testing machine (e.g., UTM7305 model) according to standard GB / T24533-2009. An exemplary test method is as follows: Weigh 1g of positive electrode active material and add it to a container with a base area of ​​1.327cm². 2 In the mold, pressure was applied to 200 kg (equivalent to 2 kN), held for 30 seconds, then depressurized and held for 10 seconds. The compacted density of the positive electrode active material under 2 kN pressure was then recorded and calculated. In this application, the compacted density of the positive electrode active material was measured under 2 kN pressure.

[0111] The volumetric particle size distribution (Dv50) and specific surface area can both be determined by laser diffraction particle size analysis, referring to standard GB / T 19077-2016, using a laser particle size analyzer (e.g., Malvern Master Size 3000).

[0112] The powder resistivity of the positive electrode active material can be tested using a powder resistivity tester (ST2722) and analyzed and tested according to the standard GB / T 30835-2014.

[0113] In this application, the various parameter tests for the positive electrode active material can be performed directly on the positive electrode active material or by sampling from a single battery cell.

[0114] When the test sample is obtained from a single battery cell, as an example, the sampling can be performed according to the following steps: Discharge the battery cell (generally to a fully discharged state), remove the positive electrode after disassembling the battery cell, and soak the positive electrode in dimethyl carbonate (DMC) for a certain period of time (e.g., 2-10 hours); then remove the positive electrode and dry it at a certain temperature and time (e.g., 60°C, 4h), and remove the positive electrode after drying; bake the dried positive electrode at a certain temperature and time (e.g., 400°C, 2h), select a region from the baked positive and negative electrode cells, and sample the positive active material (sampling can be done by scraping powder with a blade); sieve the collected positive active material (e.g., sieve through a 200-mesh sieve), and finally obtain a positive active material sample that can be used to test the material parameters mentioned above in this application.

[0115] Another embodiment of this application provides a method for preparing a positive electrode active material, which may include the following steps:

[0116] S10 provides a carbon source, a transition metal carbide, and a solution based on the chemical formula LiFe. 1-x-y Mn x M y PO4 provides raw materials containing lithium phosphate, wherein 0≤x≤1, 0≤y<1, 0≤1-xy≤1, and M is selected from one or more elements of Group IIA, Group IIIA, Group IVA, and transition metals; the raw materials containing lithium phosphate include at least one of iron source and manganese source, lithium source, and phosphorus source;

[0117] S20, mix the iron source and / or manganese source with the carbon source for a first sintering treatment to obtain the first sintered material;

[0118] S30 involves mixing the first sintering material, lithium source, phosphorus source, and transition metal carbide, and then performing a second sintering process to obtain the positive electrode active material.

[0119] The method for preparing the positive electrode active material provided in this application involves first performing a sintering treatment on a carbon source, an iron source, and / or a manganese source. This allows the carbon material to be pre-coated onto the lithium phosphate-containing raw material. During subsequent calcination, the carbon material can then coat the surface of the primary lithium phosphate particles, improving the coating effect. Simultaneously, the manganese and iron sources act as "graphitization promoters" for the carbon material, accelerating its graphitization and increasing the degree of graphitization in the carbon coating layer, thereby further enhancing its point conductivity.

[0120] According to the embodiments of this application, in preparing the positive electrode active material, the carbon source is first pre-sintered with a manganese source and / or an iron source, and then mixed with other raw materials and transition metal carbides for a secondary sintering treatment. This allows the carbon material to better coat the surface of the primary particles and the transition metal carbides to coat the surface of the secondary particles, forming a positive electrode active material structure with lithium phosphate and carbon material as the core and transition metal carbides as the coating material. Therefore, the preparation method provided in the embodiments of this application can be used to prepare the positive electrode active material provided in the above embodiments of this application.

[0121] In some embodiments, the carbon source may include one or more of glucose, sucrose, starch, tannic acid, phenolic resin, polyvinyl alcohol, polyethylene glycol, maltose, and cyclodextrin.

[0122] In some embodiments, the iron source may include one or more of the following: ferric hydroxide, iron(II) oxide, ferric oxide, ferrous phosphate, ferric phosphate, ferrous oxalate, ferric acetate, and ferric sulfate.

[0123] In some embodiments, the manganese source may include one or more of manganese nitrate, manganese acetate, manganese phosphate, manganese oxalate, manganese carbonate, and ammonium manganese phosphate.

[0124] In some embodiments, the lithium source may include one or both of lithium carbonate and lithium oxalate.

[0125] In some embodiments, the phosphorus source may include one or more of phosphoric acid, ferric phosphate, ferrous phosphate, ferrous ammonium phosphate, ammonium dihydrogen phosphate, ammonium monohydrogen phosphate, ammonium phosphate, lithium monohydrogen phosphate, and lithium dihydrogen phosphate.

[0126] In this application, transition metal carbides can be obtained commercially or prepared from transition metal carbide precursors.

[0127] In some embodiments, transition metal carbides can be prepared using transition metal carbide precursors as raw materials. Transition metal carbides are prepared by exfoliating the precursors with a strong acid solvent. The strong acid exfoliation removes impurities from the precursors and simultaneously generates numerous exposed active functional groups (such as hydroxyl, carboxyl, and ether groups) on the surface of the transition metal carbides. These exposed active functional groups can form covalent bonds such as "metal-OC" and "metal-O-transition metal" with the exposed metal atoms on the surface of lithium phosphate particles. These covalent bonds exhibit strong interfacial interactions, thereby enhancing the bonding strength of the transition metal carbides within the core, improving coating stability, reducing the detachment of the coating material from the core during charging and discharging, improving cycle stability, and ultimately improving the cycle performance of the battery cell.

[0128] In some embodiments, the strong acid may include one or more of hydrochloric acid, sulfuric acid, and hydrofluoric acid.

[0129] In some embodiments, the transition metal carbide may include a lithium-modified transition metal carbide.

[0130] Lithium ions can be introduced during the preparation of transition metal carbides. Specifically, the lithium source and the transition metal carbide precursor can be mixed in a strong acid solvent for reaction.

[0131] In some embodiments, the mass ratio of transition metal carbide precursor to lithium salt can be 1:(0.2-1).

[0132] By introducing lithium ions, "Li-OH" bonds can be formed with hydroxyl groups on the surface of transition metal carbide, forming lithium-modified transition metal carbide. The introduction of lithium ions can improve the dispersibility and self-aggregation of transition metal carbide, which is conducive to the formation of a uniform and dense coating layer on the surface of lithium phosphate core. This can reduce the direct contact between the core and the electrolyte, reduce electrolyte side reactions, and further improve the cycle performance of the battery cell.

[0133] In some embodiments, the mass content of the carbon source can be 0.5%-1.5% based on the total mass of the first sinter. Exemplarily, the mass content of the carbon source can be 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1.0%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, or any range of the above values, based on the total mass of the first sinter.

[0134] In some embodiments, the mass content of transition metal carbides can be 0.1%-1% based on the total mass of the positive electrode active material. Exemplarily, the mass content of transition metal carbides can be 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1.0%, or any range of the above values, based on the total mass of the positive electrode active material.

[0135] In some embodiments, in step S20, the temperature of the first sintering treatment can be 600℃-800℃, the time of the first sintering treatment can be 5h-10h, and the heating rate can be 1℃ / min-5℃ / min.

[0136] In some embodiments, in step S30, the temperature of the second sintering treatment can be 700℃-800℃, the time of the second sintering treatment can be 6h-12h, and the heating rate can be 1℃ / min-5℃ / min.

[0137] In some embodiments, the positive electrode active material may further include one or more of layered lithium-containing transition metal oxides, Prussian blue compounds, polyanionic compounds, and sodium transition metal oxides.

[0138] Examples of layered lithium-containing transition metal oxides may include one or more of lithium cobalt oxides, lithium nickel oxides, lithium manganese oxides, lithium nickel cobalt oxides, lithium manganese cobalt oxides, lithium nickel manganese oxides, lithium nickel cobalt manganese oxides, lithium nickel cobalt aluminum oxides, and their respective modified compounds.

[0139] In some embodiments, the layered lithium-containing transition metal oxide may include Ni. The molar amount of Ni may account for more than 70% of the total molar amount of transition metal elements in the layered lithium-containing transition metal oxide; optionally, the molar amount of Ni may account for more than 80% of the total molar amount of transition metal elements in the layered lithium-containing transition metal oxide; more preferably, the molar amount of Ni may account for more than 90% of the total molar amount of transition metal elements in the layered lithium-containing transition metal oxide.

[0140] The higher the Ni content in layered lithium-containing transition metal oxides, the higher the energy density of the battery cell.

[0141] In some embodiments, layered lithium-containing transition metal oxides may include Li a Ni b Co c M d O e A fWherein, 0 < a ≤ 1.2; 0.8 ≤ b < 1; 0 < c < 1; 0 < d < 1; b + c + d = 1; 1 ≤ e ≤ 2; 0 ≤ f ≤ 1; M includes, but is not limited to, one or more of Mn, Al, Zr, Zn, Cu, Cr, Mg, Fe, V, Ti, and B; A includes, but is not limited to, one or more of N, F, S, and Cl. This can further improve the energy density of individual battery cells.

[0142] In some embodiments, as an example, layered lithium-containing transition metal oxides may include, but are not limited to, LiNi. 0.8 Co 0.1 Mn 0.1 O2, LiNi 0.8 Co 0.15 Al 0.05 O2, LiNi 0.9 Co 0.06 Mn 0.04 O2, LiNi 0.92 Co 0.06 Mn 0.02 O2, LiNi 0.96 Co 0.02 Mn 0.02 O2, LiNi 0.96 Co 0.02 Mn 0.02 O2N 0.02 One or more of them.

[0143] During the charging and discharging process of a battery cell, Li undergoes insertion / extraction and consumption, resulting in varying molar Li content at different discharge states. In the examples of positive electrode active materials in this application, the molar Li content refers to the initial state of the material, i.e., the state before feeding. After charge-discharge cycles, the molar Li content may change when the positive electrode active material is applied to the battery cell.

[0144] In some embodiments, as an example, sodium transition metal oxides may include, but are not limited to:

[0145] Na 1-x Cu h Fe k Mn l M 1 m O 2-y M 1 It is one or more of Li, Be, B, Mg, Al, K, Ca, Ti, Co, Ni, Zn, Ga, Sr, Y, Nb, Mo, In, Sn, and Ba, 0 <x≤0.33,0<h≤0.24,0≤k≤0.32,0<l≤0.68,0≤m<0.1,h+k+l+m=1,0≤y<0.2;

[0146] Na 0.67 Mn 0.7 Ni z M 2 0.3-z O2, where M 2 It is one or more of Li, Mg, Al, Ca, Ti, Fe, Cu, Zn and Ba, 0 <z≤0.1;

[0147] Na a Li b Ni c Mn d Fe e O2, of which 0.67 <a≤1,0<b<0.2,0<c<0.3,

[0148] 0.67 <d+e<0.8,b+c+d+e=1。

[0149] In some embodiments, as an example, the polyanionic compound may include, but is not limited to:

[0150] A 1 f M 3 g (PO4) i O j X 1 3-j Where A is one or more of H, Li, Na, K, and NH4, and M 3 It is one or more of Ti, Cr, Mn, Fe, Co, Ni, V, Cu and Zn, X 1 It is one or more of F, Cl and Br, 0 <f≤4,0<g≤2,1≤i≤3,0≤j≤2;

[0151] Na n M 4 PO4X 2 M 4 It is one or more of Mn, Fe, Co, Ni, Cu and Zn, X 2 It is one or more of F, Cl and Br, 0 <n≤2;

[0152] Na p M 5 q (SO4)3, where M 5 It is one or more of Mn, Fe, Co, Ni, Cu and Zn, 0 <p≤2,0<q≤2;

[0153] Na s Mn t Fe3-t (PO4)2(P2O7), where 0 < s ≤ 4, 0 ≤ t ≤ 3, for example, t is 0, 1, 1.5, 2, or 3.

[0154] In some embodiments, by way of example, Prussian blue compounds may include, but are not limited to:

[0155] A u M 6 v [M 7 (CN)6] w ·xH2O, where A is H + 、NH4 + 、an alkali metal cation, or an alkaline earth metal cation, or one or more of them, M 6 and M 7 are each independently one or more of transition metal cations, 0 < u ≤ 2, 0 < v ≤ 1, 0 < w ≤ 1, 0 < x < 6. For example, A is H + 、Li + 、Na + 、K + 、NH4 + 、Rb + 、Cs + 、Fr + 、Be 2+ 、Mg 2+ 、Ca 2+ 、Sr 2+ 、Ba 2+ 、and Ra 2+ or one or more of them, M 6 and M 7 are each independently cations of one or more transition metal elements selected from Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Zn, Sn, and W. Optionally, A is Li + 、Na + 、and K + or one or more of them, M 6 is one or more cations of transition metal elements selected from Mn, Fe, Co, Ni, and Cu, and M 7 is one or more cations of transition metal elements selected from Mn, Fe, Co, Ni, and Cu.

[0156] In the enumeration of the positive electrode active materials in the embodiments of the present application, the molar content of O is only the theoretical value, and the release of oxygen from the lattice will cause the molar content of O to change, and the actual molar content of O will fluctuate.

[0157] The modified compounds of the above positive electrode active materials may be doping modification and / or surface coating modification of the positive electrode active materials.

[0158] In some embodiments, the positive electrode film layer may optionally include a binder. As an example, the binder may include one or more of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), PVDF-tetrafluoroethylene-propylene terpolymer, PVDF-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, and fluorinated acrylate resins.

[0159] In some implementations, the weight percentage of the binder in the positive electrode film layer is greater than or equal to 0.5%, which is beneficial for obtaining good adhesion performance.

[0160] In some embodiments, the positive electrode film layer further includes a conductive agent. As an example, the conductive agent may include one or more of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.

[0161] In some embodiments, the positive current collector may be a metal foil or a composite current collector. For example, aluminum foil may be used as the metal foil. The composite current collector may include a polymer substrate and a metal layer formed on at least one surface of the polymer substrate. The composite current collector may be made by forming a metal material, such as aluminum, aluminum alloy, copper, nickel, nickel alloy, titanium, titanium alloy, silver, and silver alloy, on the polymer substrate. The polymer substrate may include polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), and other substrates.

[0162] In some embodiments, the thickness of the positive current collector is from 4 μm to 20 μm. It is optionally from 6 μm to 18 μm, and more preferably from 8 μm to 16 μm.

[0163] In some embodiments, the positive electrode sheet can be prepared by dispersing the above-mentioned components for preparing the positive electrode sheet, such as positive active material, conductive agent, binder and any other components, in a solvent (e.g., N-methylpyrrolidone) to form a positive electrode slurry; coating the positive electrode slurry onto the positive electrode current collector, and then obtaining the positive electrode sheet after drying, cold pressing and other processes.

[0164] [Negative electrode plate]

[0165] In some embodiments, the negative electrode sheet includes a negative current collector and a negative electrode film layer located on at least one side of the negative current collector, the negative electrode film layer including a negative electrode active material.

[0166] As an example, the negative electrode current collector has two surfaces opposite each other in its own thickness direction, and the negative electrode film layer is disposed on either or both of the two opposite surfaces of the negative electrode current collector. The negative electrode current collector can be made of materials such as metal foil, carbon-coated metal foil, or porous metal plate, and copper foil is an option.

[0167] As an example, the negative electrode active material may include one or more of the following: artificial graphite, natural graphite, mesophase micro carbon spheres, hard carbon, soft carbon, silicon, and silicon-carbon composites.

[0168] Silicon-based composite materials can be prepared by methods known in the art. For example, they can be prepared by vapor deposition using graphite and silicon materials as raw materials.

[0169] In some embodiments, the negative electrode film layer may further include a negative electrode conductive agent. As an example, the negative electrode conductive agent may include, but is not limited to, one or more of superconducting carbon, conductive graphite, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.

[0170] In some embodiments, the negative electrode film layer may further include a negative electrode binder. As an example, the negative electrode binder may include, but is not limited to, one or more of styrene-butadiene rubber (SBR), water-soluble unsaturated resin SR-1B, waterborne acrylic resins (e.g., polyacrylic acid PAA, polymethacrylic acid PMAA, sodium polyacrylate PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), and carboxymethyl chitosan (CMCS).

[0171] In some embodiments, the negative electrode film layer may also include other additives. As an example, other additives may include thickeners, such as sodium carboxymethyl cellulose (CMC-Na), PTC thermistor materials, etc.

[0172] In some embodiments, the negative electrode current collector may be a metal foil or a composite current collector. Examples of metal foils include copper foil, copper alloy foil, aluminum foil, and aluminum alloy foil. The composite current collector may include a polymeric material substrate and a metal material layer formed on at least one side of the polymeric material substrate. Examples of metal materials include, but are not limited to, one or more of copper, copper alloys, nickel, nickel alloys, titanium, titanium alloys, silver, and silver alloys. Examples of polymeric material substrates include, but are not limited to, one or more of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), and polyethylene (PE).

[0173] The negative electrode sheet does not exclude other additional functional layers besides the negative electrode film layer. For example, in some embodiments, the negative electrode sheet may also include a conductive undercoat layer sandwiched between the negative electrode current collector and the negative electrode film layer and located on the surface of the negative electrode current collector, which may be composed of a conductive agent and a binder; in some embodiments, the negative electrode sheet may also include a protective layer covering the surface of the negative electrode film layer.

[0174] The negative electrode sheet can be prepared as follows: The negative electrode active material, negative electrode binder, negative electrode conductive agent, and optional other additives are dispersed in a solvent and stirred evenly to form a negative electrode slurry; the negative electrode slurry is coated onto a negative electrode current collector, and after drying, rolling, and other processes, a negative electrode sheet is formed. The solvent can be N-methylpyrrolidone (NMP) or deionized water, but is not limited to these.

[0175] [Isolation Component]

[0176] In some embodiments, the electrode assembly further includes an isolator disposed between the positive and negative electrodes.

[0177] In some embodiments, the isolation chamber includes an isolation membrane. This application does not impose any particular limitation on the type of isolation membrane; any known porous membrane with good chemical and mechanical stability can be selected.

[0178] In some embodiments, the material of the separator may include at least one selected from glass fiber, nonwoven fabric, polyethylene, polypropylene, and polyvinylidene fluoride. The separator may be a single-layer film or a multi-layer composite film, without particular limitation. When the separator is a multi-layer composite film, the materials of each layer may be the same or different, without particular limitation. The separator may be a single component located between the positive and negative electrodes, or it may be attached to the surfaces of the positive and negative electrodes. An inorganic particle coating, an organic particle coating, or an organic / inorganic composite coating may also be applied to the surface of the separator.

[0179] In some embodiments, the separator is a solid electrolyte. The solid electrolyte is disposed between the positive and negative electrodes, serving both to transport ions and to isolate the positive and negative electrodes.

[0180] [Electrolytes]

[0181] In some embodiments, the electrolyte is an electrolyte solution, which includes an electrolyte salt and an organic solvent.

[0182] In some embodiments, the electrolyte includes anion, which may include bis(fluorosulfonyl)imide anion (FSI). - ), bis(trifluoromethanesulfonyl)imide anion (TFSI) - ), dioxaborate anion (BOB) - ), difluorooxalate borate anion (DFOB) - ), difluorodioxanol phosphate anion (DFOP) - ), tetrafluorooxalate phosphate anion (TFOP) - ), difluorophosphate anion (PO2F2) - ), hexafluorophosphate anion (PF6) - ), tetrafluoroborate anion (BF4) -), hexafluoroarsenate anion (AsF6) - ), trifluoromethanesulfonate anion (CF3SO3) - One or more of the following.

[0183] In some embodiments, the electrolyte includes cations, which may include one or more of lithium ions and sodium ions.

[0184] In some embodiments, the concentration of the electrolyte salt may be 0.3 mol / L or higher, optionally 0.7 mol / L or higher, and further optionally 4 mol / L or lower, optionally 2.5 mol / L or lower, or 1.7 mol / L or lower. When the concentration of the electrolyte salt is within the above range, the electrolyte can have a suitable ionic conductivity.

[0185] Organic solvents may include, but are not limited to, one or more of esters, ethers, sulfones, and nitriles. Esters may include, but are not limited to, one or more of carbonates, phosphate esters, carboxylic esters, sulfate esters, and sulfonates. Carbonates may include cyclic carbonates and / or chain carbonates; optionally, carbonates may include both cyclic and chain carbonates. Chain carbonates may include low-viscosity polar chain carbonates, aliphatic branched carbonates, etc.

[0186] As examples, organic solvents may include methyl formate (MF), methyl acetate (MA), ethyl acetate (EA), propyl acetate (PA), methyl propionate (MP), ethyl propionate (EP), propyl propionate (PP), methyl butyrate (MB), ethyl butyrate (EB), 1,4-butyrolactone (GBL), sulfolane (SF), dimethyl sulfone (MSM), methyl ethyl sulfone (EMS), diethyl sulfone (ESE), dimethyl ether tetraethylene glycol (TEGDME), ethylene glycol dimethyl ether (DME), 1,3-dioxolane (DOL), trimethyl phosphate, 3-methoxypropionitrile, H(CF2)2OCH3, C4F9OCH3, H(CF2)2OCH2CH3, H(CF2)2OCH2CF3, H(CF2)2CH2O(CF2)2H, CF3CHFC F2OCH3, CF3CHFCF2OCH2CH3, 2-trifluoromethylhexafluoropropyl methyl ether, 2-trifluoromethylhexafluoropropyl ethyl ether, 2-trifluoromethylhexafluoropropyl propyl ether, 3-trifluoromethyloctafluorobutyl methyl ether, 3-trifluoromethyloctafluorobutyl ethyl ether, 3-trifluoromethyloctafluorobutyl propyl ether, 4-trifluoromethyldecafluoropentyl methyl ether, 4-trifluoromethyldecafluoropentyl ethyl ether, 4-trifluoromethyldecafluoropentyl propyl ether, 5-trifluoromethyldodecylfluorohexyl methyl ether, 5-trifluoromethyldodecylfluorohexyl ethyl ether, 5-trifluoromethyldodecylfluorohexyl propyl ether, 6-trifluoromethyltetradecylfluoroheptyl methyl ether, 6-trifluoromethyltetradecylfluoroheptyl ethyl ether, 6-trifluoromethyltetradecylfluoroheptyl propyl ether, 7-trifluoromethylhexadecylfluorooctyl methyl ether, 7-trifluoromethylhexadecylfluorooctyl ethyl ether, 7-trifluoromethylhexadecylfluorooctyl propyl ether.

[0187] In some embodiments, the electrolyte includes anion, which may include bis(fluorosulfonyl)imide anion (FSI). - ), bis(trifluoromethanesulfonyl)imide anion (TFSI) - ), dioxaborate anion (BOB) - ), difluorooxalate borate anion (DFOB) - ), difluorodioxanol phosphate anion (DFOP) - ), tetrafluorooxalate phosphate anion (TFOP) - ), difluorophosphate anion (PO2F2) - ), hexafluorophosphate anion (PF6) - ), tetrafluoroborate anion (BF4) - ), hexafluoroarsenate anion (AsF6) - ), trifluoromethanesulfonate anion (CF3SO3) - One or more of the following.

[0188] In some embodiments, the electrolyte includes cations, which may include one or more of lithium ions and sodium ions.

[0189] In some embodiments, the concentration of the electrolyte salt may be 0.3 mol / L or higher, optionally 0.7 mol / L or higher, and further optionally 4 mol / L or lower, optionally 2.5 mol / L or lower, or 1.7 mol / L or lower. When the concentration of the electrolyte salt is within the above range, the electrolyte can have a suitable ionic conductivity.

[0190] In some embodiments, the additive may also include negative electrode film-forming additives, positive electrode film-forming additives, and additives that can improve certain battery performance, such as additives that improve battery overcharge performance, additives that improve battery high-temperature performance, and additives that improve battery low-temperature power performance.

[0191] Example

[0192] The following embodiments describe the disclosure of this application in more detail. These embodiments are merely illustrative, as various modifications and variations will be apparent to those skilled in the art within the scope of the disclosure of this application. Unless otherwise stated, all parts, percentages, and ratios reported in the following embodiments are based on mass, and all reagents used in the embodiments are commercially available or synthesized by conventional methods and can be used directly without further processing, and the instruments used in the embodiments are commercially available.

[0193] Example 1

[0194] Positive electrode active material

[0195] 15.5g of transition metal carbide precursor Ti3AlC2 and lithium source Li2CO3 were added sequentially to 100ml of 5mol / L hydrochloric acid. The mixture was sonicated at 45℃ for 2h to remove the aluminum layer. The product was then washed with deionized water and centrifuged several times until the pH of the supernatant was around 6. The product was then vacuum dried at 85℃ for 8h to obtain lithium-modified Ti3C2.

[0196] 1290.1g of manganese source MnSO4-2H2O, 1414.7g of iron source FeSO4-2H2O, and 75g of carbon source glucose were added sequentially to a reactor containing deionized water and stirred thoroughly at 200 rpm for 2 hours to obtain a slurry. The slurry was then passed into a sand mill for grinding using 0.6mm zirconium beads for 5 hours. The ground slurry was then dried using a spray dryer with an inlet temperature of 200℃ and an outlet temperature of 110℃ to obtain a powder. This powder was placed in a crucible and then placed in a box furnace, heated to 600℃ at a heating rate of 5℃ / min, held at that temperature for 10 hours, and then cooled to obtain the MnSO4 / FeSO4@C material.

[0197] 1362.5g of the MnSO4 / FeSO4@C material prepared above, 245.8g of lithium source Li2CO3, 748.3g of phosphorus source H3PO4, and 5.0g of lithium-modified Ti3C2 prepared above were sequentially added to a reactor containing 4L of deionized water and stirred thoroughly. The stirring rate was controlled at 200rpm, and the mixture was stirred for 2 hours to obtain a slurry. The slurry was then passed through a sand mill for grinding using 0.6mm zirconium beads for 5 hours. The ground slurry was then spray-dried using a spray dryer with an inlet temperature of 200℃ and an outlet temperature of 110℃ to obtain powder. The powder was placed in a crucible and then placed in a box furnace, heated to 700℃ at a heating rate of 5℃ / min, held at that temperature for 12 hours, and then cooled to obtain the positive electrode active material. The core of the positive electrode active material includes LiFe 0.4 Mn 0.6 PO4 and carbon.

[0198] Positive electrode sheet

[0199] The positive electrode active material, conductive carbon black, and polyvinylidene fluoride (PVDF) prepared above are mixed in a mass ratio of 8:1:1 and then added to the solvent N-methylpyrrolidone (NMP) to uniformly disperse and obtain a positive electrode slurry. The positive electrode slurry is coated onto the surface of the positive electrode current collector aluminum foil, and then dried, cold-pressed, and slit to obtain the positive electrode sheet.

[0200] Negative electrode sheet

[0201] A negative electrode slurry is prepared by uniformly mixing graphite (a negative electrode active material), conductive carbon black (a conductive agent), sodium carboxymethyl cellulose (CMC-Na) (a thickener), and styrene-butadiene rubber (SBR) (a binder) in deionized water at a mass ratio of 95:1:1:3. The negative electrode slurry is then uniformly coated onto copper foil (a negative electrode current collector), and the negative electrode sheet is obtained by cold pressing and slitting.

[0202] Separating membrane

[0203] A polyethylene (PE) film with a thickness of 12μm was selected.

[0204] electrolyte

[0205] Ethylene carbonate, diethyl carbonate, and dimethyl carbonate were mixed in a volume ratio of 1:1:1. Lithium hexafluorophosphate (LiPF6) was dissolved in the mixture to obtain the electrolyte. The concentration of LiPF6 in the electrolyte was 1 mol / L.

[0206] battery cell

[0207] The positive electrode, negative electrode, and separator are stacked in sequence and then injected with electrolyte to obtain a coin cell.

[0208] Examples 2-8

[0209] The preparation of the battery cell is similar to that in Example 1, except that the parameters of the positive electrode active material are adjusted. For details of the parameter adjustments, please refer to Table 1.

[0210] Table 1

[0211]

[0212] Example 9

[0213] The difference from Example 1 lies in the preparation method of the transition metal carbide. The specific preparation method is as follows: 15.5g of the transition metal carbide precursor Ti3AlC2 was added to 100ml of 5mol / L hydrochloric acid and sonicated at 45℃ for 2h to remove the aluminum layer. The product was then washed with deionized water and centrifuged several times until the pH of the supernatant was around 6. The product was then vacuum dried at 85℃ for 8h to obtain Ti3C2.

[0214] All of them are consistent with those in Example 1.

[0215] Comparative Example 1

[0216] The difference from Example 1 lies in the preparation method of the positive electrode active material, which is as follows:

[0217] Positive electrode active material

[0218] 15.5g of transition metal carbide precursor Ti3AlC2 and lithium source Li2CO3 were added sequentially to 100ml of 5mol / L hydrochloric acid. The mixture was sonicated at 45℃ for 2h to remove the aluminum layer. The product was then washed with deionized water and centrifuged several times until the pH of the supernatant was around 6. The product was then vacuum dried at 85℃ for 8h to obtain lithium-modified Ti3C2.

[0219] 645.0g of manganese source MnSO4-H2O, 707.3g of iron source FeSO4-7H2O, 245.8g of lithium source Li2CO3, 748.3g of phosphorus source H3PO4, 5.0g of lithium-modified Ti3C2 prepared above, and 37.5g of carbon source glucose were added sequentially to a reactor containing deionized water and stirred thoroughly at a stirring rate of 200 rpm for 2 hours to obtain a slurry. The slurry was then passed through a sand mill for grinding using 0.6mm zirconium beads for 5 hours. The ground slurry was then dried using a spray dryer with an inlet temperature of 200℃ and an outlet temperature of 110℃ to obtain a powder. This powder was placed in a crucible and then placed in a box furnace, heated to 700℃ at a heating rate of 5℃ / min, held at that temperature for 12 hours, and then cooled to obtain the positive electrode active material.

[0220] Everything else is the same as in Example 1.

[0221] Comparative Example 2

[0222] The difference from Example 1 lies in the preparation method of the positive electrode active material, which is as follows:

[0223] 1290.1g of manganese source MnSO4-H2O, 1414.7g of iron source FeSO4-7H2O, and 75g of carbon source glucose were added sequentially to a reactor containing deionized water and stirred thoroughly at 200 rpm for 2 hours to obtain a slurry. The slurry was then passed through a sand mill for grinding using 0.6mm zirconium beads for 5 hours. The ground slurry was then dried using a spray dryer with an inlet temperature of 200℃ and an outlet temperature of 110℃ to obtain a powder. This powder was placed in a crucible and then placed in a box furnace, heated to 600℃ at a heating rate of 5℃ / min, held at that temperature for 10 hours, and then cooled to obtain the MnSO4 / FeSO4@C material.

[0224] 1362.5g of the prepared MnSO4 / FeSO4@C material, 245.8g of lithium source Li2CO3, and 748.3g of phosphorus source H3PO4 were sequentially added to a reactor containing 4L of deionized water and stirred thoroughly. The stirring rate was controlled at 200rpm, and the mixture was stirred for 2 hours to obtain a slurry. The slurry was then passed through a sand mill for grinding using 0.6mm zirconium beads for 5 hours. The ground slurry was then spray-dried using a spray dryer with an inlet temperature of 200℃ and an outlet temperature of 110℃ to obtain powder. The powder was placed in a crucible and then placed in a box furnace, heated to 700℃ at a heating rate of 5℃ / min, held at that temperature for 12 hours, and then cooled to obtain the positive electrode active material. The core of the positive electrode active material includes LiFe 0.4 Mn0.6 PO4 and carbon.

[0225] Everything else is the same as in Example 1.

[0226] Comparative Example 3

[0227] 15.5g of transition metal carbide precursor Ti3AlC2 and lithium source Li2CO3 were added sequentially to 100ml of 5mol / L hydrochloric acid. The mixture was sonicated at 45℃ for 2h to remove the aluminum layer. The product was then washed with deionized water and centrifuged several times until the pH of the supernatant was around 6. The product was then vacuum dried at 85℃ for 8h to obtain lithium-modified Ti3C2.

[0228] 1290.1g of manganese source MnSO4-H2O, 1414.7g of iron source FeSO4-7H2O, 245.8g of lithium source Li2CO3, 748.3g of phosphorus source H3PO4, and 5.0g of the lithium-modified Ti3C2 prepared above were sequentially added to a reactor containing 4L of deionized water and stirred thoroughly. The stirring rate was controlled at 200 rpm, and the mixture was stirred for 2 hours to obtain a slurry. The slurry was then passed through a sand mill for grinding using 0.6mm zirconium beads for 5 hours. The ground slurry was then dried using a spray dryer with an inlet temperature of 200℃ and an outlet temperature of 110℃ to obtain a powder. The powder was placed in a crucible and then placed in a box furnace, heated to 700℃ at a heating rate of 5℃ / min, held at that temperature for 12 hours, and then cooled to obtain the positive electrode active material.

[0229] Test section

[0230] 1. Powder resistivity of positive electrode active material

[0231] Weigh 1g of sample and place it in the mold. Then place the mold in a four-probe resistivity tester and adjust the pressure to 8.0MPa. After the mold height and pressure are stable, test the forward resistivity and reverse resistivity of the sample respectively, and take the average of the two as the powder resistivity of the sample.

[0232] 2. Stability of the positive electrode active material

[0233] Weigh 5g of sample and place it in 100g of deionized water. Sonicate the sample at 20000Hz for 30 minutes, then dry it to obtain the ultrasonicated sample. Measure the powder resistivity of the sample before and after ultrasonication.

[0234] 3. Capacity

[0235] The Shenzhen Xinwei Battery Testing System was used to cycle charge and discharge the coin cells at 0.1C and 1C charge and discharge rates. The test temperature was 25.0℃ and the charge and discharge voltage was 2.0V-4.3V. The charge and discharge capacity of the first cycle was obtained. The ratio of the discharge capacity to the mass of the positive electrode active material is the specific capacity.

[0236] 4. Capacity retention rate

[0237] The Shenzhen Xinwei Battery Testing System was used to perform cyclic charging and discharging of coin cells at a 1C charge-discharge rate for 2000 cycles. The test temperature was 25.0℃, and the charge-discharge voltage was 2.0V-4.3V. The capacity retention rate was obtained by dividing the discharge capacity of the last cycle by the discharge capacity of the first cycle.

[0238] The test results are detailed in Table 2.

[0239] Table 2

[0240]

[0241] Based on the data from Examples 1-4 and Comparative Examples 1-3 in Table 2, the embodiments of this application utilize transition metal carbides as coating materials, simultaneously coating the carbon material in the core onto the surface of the primary particles. This effectively reduces the powder resistivity of the positive electrode active material, improves its conductivity, and enhances the cycle performance of the three-cell battery. Furthermore, in Examples 1-4, adjusting the mass content of the transition metal carbide Ti3C2 further improves the conductivity of the positive electrode active material, further enhancing the cycle performance of the battery cell. Performance is optimal when the Ti3C2 mass content is 0.5%. When the addition amount is 0.1%, the conductivity deteriorates, the powder resistivity increases, and both the specific capacity and capacity retention decrease. When the addition amount is 1%, conductivity improves, and the powder resistivity decreases slightly; however, Ti3C2, as an inactive material, cannot contribute to capacity, and the specific capacity decreases with increasing addition amount. In summary, the difference in electrical performance between 1% and 0.5% addition amounts is not significant.

[0242] In Examples 6 and 7, the carbon content in the core was adjusted. It can be seen that as the carbon content in the phosphate cathode material increases, the conductivity and specific capacity increase accordingly. In Example 1, the electrochemical performance was better when the carbon content was 0.75%.

[0243] Example 9, which did not introduce lithium ions during the preparation of Ti3C2, showed poorer performance compared to Example 1. This indicates that introducing lithium ions during the preparation of Ti3C2 allows them to form Li-OH bonds with the hydroxyl groups on the Ti3C2 surface, resulting in lithium-modified Ti3C2. This improves dispersibility and self-aggregation, and allows the construction of a uniform and dense coating layer on the surface of the lithium manganese iron phosphate substrate. This reduces direct contact between the substrate and the electrolyte, decreases side reactions, and improves cycle stability.

[0244] It should be noted that this application is not limited to the above-described embodiments. The above embodiments are merely examples, and any embodiments with the same structure and effect as the technical concept within the scope of this application are included in the technical scope of this application. Furthermore, various modifications that can be conceived by those skilled in the art to the embodiments, and other ways of constructing by combining some of the constituent elements of the embodiments, without departing from the spirit of this application, are also included in the scope of this application.

Claims

1. A battery cell, characterized in that, The positive electrode includes a positive current collector and a positive electrode film layer located on at least one side of the positive current collector. The positive electrode film layer includes a positive electrode active material, which includes: The core, comprising carbon materials and the chemical formula LiFe 1-x-y Mn x M y PO4 contains lithium phosphate, wherein 0≤x≤1, 0≤y<1, 0≤1-xy≤1, and M is selected from one or more elements of Group IIA, Group IIIA, Group IVA, and transition metals; A coating material is applied to at least a portion of the surface of the core, the coating material comprising a transition metal carbide.

2. The battery cell according to claim 1, characterized in that, The lithium phosphate comprises secondary particles formed by the stacking of primary particles, with the carbon material coating at least a portion of the surface of the primary particles.

3. The battery cell according to claim 2, characterized in that, The volume distribution particle size Dv50 of the primary particles is 50nm-600nm.

4. The battery cell according to claim 2 or 3, characterized in that, The carbon material forms a carbon coating layer on at least a portion of the surface of the primary particles, the thickness of the carbon coating layer being 1 nm to 20 nm.

5. The battery cell according to claim 4, characterized in that, The Raman spectrum of the carbon coating layer has G peaks and D peaks, and I D / I G It is 0.6-0.

9.

6. The battery cell according to any one of claims 1 to 5, characterized in that, The carbon material in the core has a mass content of 0.5%-1.5%.

7. The battery cell according to any one of claims 1 to 6, characterized in that, The coating material forms a coating layer on at least a portion of the surface of the core, and the thickness of the coating layer is 1 nm-20 nm.

8. The battery cell according to any one of claims 1 to 7, characterized in that, Based on the total mass of the positive electrode active material, the mass content of the transition metal carbide is 0.1%-1%.

9. The battery cell according to any one of claims 1 to 8, characterized in that, The transition metal carbides include one or more of titanium carbide, niobium carbide, vanadium carbide, and molybdenum carbide.

10. The battery cell according to any one of claims 1 to 9, characterized in that, The positive electrode active material satisfies at least one of the following conditions: (1) The specific surface area of ​​the positive electrode active material is 10 m². 2 / g-20m 2 / g; (2) The compaction density of the positive electrode active material is 1.9 g / cm³. 3 -2.4g / cm 3 ; (3) The resistivity of the positive electrode active material is 15Ω·cm-550Ω·cm.

11. A battery device, characterized in that, Includes the battery cell according to any one of claims 1 to 10.

12. An electrical appliance, characterized in that, Includes the battery cell according to any one of claims 1 to 10 or the battery device according to claim 11.

13. A positive electrode active material, characterized in that, include: The core, comprising carbon materials and the chemical formula LiFe 1-x-y Mn x M y PO4 contains lithium phosphate, wherein 0≤x≤1, 0≤y<1, 0≤1-xy≤1, and M is selected from one or more elements of Group IIA, Group IIIA, Group IVA, and transition metals; A coating material is applied to at least a portion of the surface of the core, the coating material comprising a transition metal carbide.

14. The positive electrode active material according to claim 13, characterized in that, The lithium phosphate comprises secondary particles formed by the stacking of primary particles, with the carbon material coating at least a portion of the surface of the primary particles.

15. The positive electrode active material according to claim 13 or 14, characterized in that, The transition metal carbides include one or more of titanium carbide, niobium carbide, vanadium carbide, and molybdenum carbide.

16. The positive electrode active material according to any one of claims 13 to 15, characterized in that, The positive electrode active material satisfies at least one of the following conditions: (2) The specific surface area of ​​the positive electrode active material is 10 m². 2 / g-20m 2 / g; (3) The compaction density of the positive electrode active material is 1.9 g / cm³. 3 -2.4g / cm 3 ; (4) The resistivity of the positive electrode active material is 15Ω·cm-550Ω·cm.

17. A method for preparing a positive electrode active material, characterized in that, Includes the following steps: Provide carbon sources, transition metal carbides, and materials based on the chemical formula LiFe. 1-x-y Mn x M y PO4 provides a lithium phosphate-containing raw material, wherein 0≤x≤1, 0≤y<1, 0≤1-xy≤1, and M is selected from one or more elements of Group IIA, Group IIIA, Group IVA, and transition metals; the lithium phosphate-containing raw material includes at least one of iron and manganese sources, a lithium source, and a phosphorus source. The iron source and / or manganese source are mixed with the carbon source for a first sintering treatment to obtain a first sintered material; The first sintering material, the lithium source, the phosphorus source, and the transition metal carbide are mixed and subjected to a second sintering process to obtain the positive electrode active material.

18. The method according to claim 17, characterized in that, The step of providing transition metal carbides includes: Provides transition metal carbide precursors; The transition metal carbide precursor was mixed with a lithium salt and reacted in an acidic solution. After drying, the transition metal carbide was obtained.

19. The method according to claim 18, characterized in that, The mass ratio of the transition metal carbide precursor to the lithium salt is 1:(0.2-1).

20. The method according to any one of claims 17 to 19, characterized in that, Based on the total mass of the first sinter, the mass content of the carbon source is 0.5%-1.5%; and / or Based on the total mass of the positive electrode active material, the mass content of the transition metal carbide is 0.1%-1%.